Enhanced Road Network to Reduce the Effect of (External – External) Freight Trips on Traffic Flow - Huda Abdulameer Abbas; Hayder Abbas Obaid; Ali Abdul Ameer Alwash (Salehan Institute of Higher Education, 2022)
The transportation system is often described as the lifeblood of modern society. Roads constitute a fundamental part of this system for both passenger and freight transports, a well-functioning freight transportation system is an essential element in any successful economy. Hilla is one of the most densely populated cities in Iraq. The road network in Hilla city is under additional load due to (external - external) trips, especially freight trips by trucks passing through the city's main entrances to cross into neighboring districts and provinces. This is due to the city's strategic location, which connects Baghdad with the southern provinces, making it an important transit route. The objective of this research is to study a proposal for modifying and developing the road network in the city of Hilla by adding new roads to the current network in order to reduce the negative impact of freight trucks passing through the city, especially (external - external) trips, by using Trans CAD and ArcGIS software network analysis. The result of network analysis shows that the suggested roads will reduce the total (travel time and distance) for the same origin and destination points by 9%, and 30%, compared with the current distance and time, respectively, while improving the level of service from D to C at peak hours for freight vehicles. Doi: 10.28991/CEJ-2022-08-11-015 Full Text: PDF